Intraoperative fluid management guided by esophageal Doppler monitoring in major abdominal surgery utilizing the enhanced recovery after surgery program: a systematic review protocol. (July 2016) - Wuellner, Lindsay; Sutton, Lisa
Abstract : Review question/objective: The objectives of this review are to identify the effectiveness of esophageal Doppler monitoring (EDM) for goal-directed fluid therapy on postoperative outcomes during abdominal surgery when an enhanced recovery after surgery (ERAS) program is implemented. The specific question of this review is: does the guidance of fluid management by EDM versus fluid management without EDM affect the length of hospital stay, occurrence of postoperative infection, hemodynamic stability and 30-day postoperative complication rate in adult patients undergoing major abdominal surgery with ERAS or similar programs?